Pemanfaatan Minyak Jelantah sebagai Bahan Dasar Pembuatan Lilin Aromaterapi di Panti Asuhan Vallery - Siregar, Nurhafni; Rosadi, Mimi; Anshor, Arrini Shabrina; Saragih, Gunaria Angelina; Telaumbanua, Hanan Alfaraha Hermawan; Nasution, Hidayati Hijjah; Sinaga, Icca Fransiska; Panjaitan, Indah; Samosir, Irfan Josuwandi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is one of the largest consumers of cooking oil in the world. Cooking oil functions to conduct heat in frying food. Used cooking oil or used cooking oil can be used and utilized. Disposal of used cooking oil can also cause environmental damage. Therefore, we need to be able to utilize used cooking oil into something that has economic value for society. This program is implemented to educate children at the Vallery orphanage so they can make an innovative aromatherapy candle product using used cooking oil. This activity aims to provide understanding to the children of the Vallery Orphanage as partners in the use of used cooking oil as an ingredient for making aromatherapy candles. This aromatherapy candle can provide a step that can potentially be developed as an alternative income for nursing home managers because it has economic value. This program is implemented as a real action from the leadership project course which aims to train the ability of PPG Pre-service students to lead through service learning activities or the ability to serve the community or society. Through this program, students are expected to be able to contribute to solving problems that exist in society. The implementation method for this activity is socialization by means of a presentation and followed by training in making aromatherapy candles made from used cooking oil.